Neurogenic bowel management after spinal cord injury: Malaysian experience - Julia, P.E.; Sudin, S.S. (2013)
Objectives: To describe the bowel programmes utilized by individuals with spinal cord injury; and to determine the association between the outcome of the bowel programmes and various interventions to facilitate defecation. Study design: A cross-sectional study. Participants: Individuals with spinal cord injury who have neurogenic bowel dysfunction. Methods: Face-to-face interviews were conducted using a self-constructed questionnaire that consisted of: (i) demographic and clinical characteristics of the participants; (ii) interventions to facilitate defecation; (iii) bowel care practices; (iv) outcome of the bowel programme (incidence of incontinence and duration of the evacuation procedure); and (v) participant satisfaction with their bowel programme. Results: The majority (79.2) of subjects used multiple interventions for bowel care. Duration of the evacuation procedure was more than 60 min in 28.0 of participants. Water intake of more than 2 l/day was associated with longer duration of bowel care. Only 8.0 of participants had at least one episode of incontinence per month. The majority of participants (84.8) were satisfied with their bowel programme. Conclusion: Patients used multiple interventions to manage their bowels and spent a substantial amount of time performing bowel care. Nevertheless, the incidence of incontinence was low and satisfaction with their bowel programme was high.